2013
DOI: 10.1037/a0028520
|View full text |Cite
|
Sign up to set email alerts
|

Additive and interactive effects in semantic priming: Isolating lexical and decision processes in the lexical decision task.

Abstract: The present study sheds light on the interplay between lexical and decision processes in the lexical decision task by exploring the effects of lexical decision difficulty on semantic priming effects. In 2 experiments, we increased lexical decision difficulty by either using transposed letter wordlike nonword distracters (e.g., JUGDE; Experiment 1) or by visually degrading targets (Experiment 2). Although target latencies were considerably slowed by both difficulty manipulations, stimulus quality-but not nonwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 108 publications
(213 reference statements)
2
43
0
Order By: Relevance
“…In recent years, however, the diffusion model has increasingly attracted the attention of researchers from various other fields of psychology. Examples indicating the wide range of applications for the diffusion model include analyses of cognitive processes in such typical experimental paradigms as the lexical decision task (e.g., Yap, Balota, & Tan, 2013), sequential priming paradigms (e.g., Voss, Rothermund, Gast, & Wentura, 2013), task switching (Schmitz & Voss, 2012, or prospective memory paradigms (e.g., Boywitt & Rummel, 2012). Other applications encompass social cognitive research (e.g., Germar, Schlemmer, Krug, Voss, & Mojzisch, 2014;Klauer, Voss, Schmitz, & Teige-Mocigemba, 2007;Voss, Rothermund, & Brandtstädter, 2008), cognitive aging (e.g., McKoon & Ratcliff, 2013;Spaniol, Madden, & Voss, 2006), cognitive processes related to psychological disorders (e.g., Metin et al, 2013;Pe, Vandekerckhove, & Kuppens, 2013;White, Ratcliff, Vasey, & McKoon, 2010b), and other fields of psychology.…”
mentioning
confidence: 99%
“…In recent years, however, the diffusion model has increasingly attracted the attention of researchers from various other fields of psychology. Examples indicating the wide range of applications for the diffusion model include analyses of cognitive processes in such typical experimental paradigms as the lexical decision task (e.g., Yap, Balota, & Tan, 2013), sequential priming paradigms (e.g., Voss, Rothermund, Gast, & Wentura, 2013), task switching (Schmitz & Voss, 2012, or prospective memory paradigms (e.g., Boywitt & Rummel, 2012). Other applications encompass social cognitive research (e.g., Germar, Schlemmer, Krug, Voss, & Mojzisch, 2014;Klauer, Voss, Schmitz, & Teige-Mocigemba, 2007;Voss, Rothermund, & Brandtstädter, 2008), cognitive aging (e.g., McKoon & Ratcliff, 2013;Spaniol, Madden, & Voss, 2006), cognitive processes related to psychological disorders (e.g., Metin et al, 2013;Pe, Vandekerckhove, & Kuppens, 2013;White, Ratcliff, Vasey, & McKoon, 2010b), and other fields of psychology.…”
mentioning
confidence: 99%
“…This distributional shift has been interpreted to reflect a processing head start (Balota et al, 2008; Yap et al, 2013; for semantic categorization: De Wit & Kinoshita, 2014; 2015a) and as supporting the widely held belief that priming during visual word recognition is driven by the rapid prospective activation of related targets triggered by the prime. However, the current study shows that the observation, or lack thereof, of a distributional shift is strongly affected by the response time floor of the measure.…”
Section: Discussionmentioning
confidence: 54%
“…Balota and colleagues (2008) found that LDTs with a short SOA (250 ms) showed a priming effect on μ and σ, and when targets were visually degraded, semantic priming affected μ and τ (Balota et al, 2008; Yap et al, 2013, both experiments used an 800 ms SOA). De Wit and Kinoshita (2015a) also observed a combination of μ- and τ-based priming for a lexical decision task with visually intact targets at a short SOA using a high proportion of related trials.…”
Section: Distributional Effects Of Semantic Primingmentioning
confidence: 99%
“…Additionally, we excluded all trials with very slow or very fast responses. The cutoff point for slow responses was set at 2.5 standard deviations of the subject mean (this is a common cutoff threshold in psycholinguistic studies, see for example Yap et al 2013;Chwilla et al 2000;van Hell and Dijkstra 2002), and was calculated for every participant separately. The cutoff point for the fast responses was set at 100 ms after stimulus onset.…”
Section: Behavioral Data Analysismentioning
confidence: 99%